Effective cost estimation process for construction projects by adopting 5D BIM technology - Cai, Jiayun (Nanyang Technological University, 2023)
Project cost management is crucial for the success of construction projects. Accurate cost estimation is essential as many projects often exceed budgets due to inadequate cost management. Currently, many construction companies rely on traditional manual cost estimation methods, which are often inefficient and prone to inaccuracies. This study aims to examine the cost management in today’s construction industry, identify factors affecting construction project costs, and investigate advanced project cost management techniques to overcome the current challenges in construction projects. A questionnaire will be distributed to 80 respondents working in the construction industry to gather data and understand the adoption of project cost estimation and 5D BIM. The study will also include a case study comparing traditional cost estimation methods with digital cost estimation software to demonstrate the significance of 5D BIM technology applied in cost management for construction projects. In recent years, the global construction industry has gradually embraced the BIM concept as the demand for building information and intelligence has become a trend. BIM technology was introduced into the construction industry between 2009 to 2010; between 2010 to 2013, BIM was in the trial run-in phase to integrate with construction project demand and achieved 3D BIM modelling; after 2013, BIM can reach the stage of BIM in-depth application. The use of 5D BIM technology has effectively addressed the challenges of low efficiency and resource wastage in the traditional construction industry. In this study, the implementation of 5D BIM technology in real construction projects was analyzed, which allowed for the integration of project models, attribute information, and third-party digital software to achieve precise cost management. The case study revealed that 5D BIM technology is beneficial for VI construction projects in terms of cost estimation, addressing issues such as ineffective cost planning, accuracy in quantity take-off, and visualizing work progress. However, as the technology is still in its early stages, there is room for improvement. This study aims to highlight the current limitations of 5D BIM technology and propose potential future developments.